Climate‐driven changes in winter abundance of a migratory waterbird in relation to EU protected areas. Issue 5 (15th January 2015) - Pavón‐Jordán, Diego; Fox, Anthony D.; Clausen, Preben; Dagys, Mindaugas; Deceuninck, Bernard; Devos, Koen; Hearn, Richard D.; Holt, Chas A.; Hornman, Menno; Keller, Verena; Langendoen, Tom; Ławicki, Łukasz; et al.
Abstract Aim Species are responding to climate change by changing their distributions, creating debate about the effectiveness of existing networks of protected areas. As a contribution to this debate, we assess whether regional winter abundances and distribution of the Smew Mergellus albellus, a migratory waterbird species listed on Annex I (EU Birds Directive) that overwinters exclusively in European wetlands, changed during 1990–2011, the role of global warming in driving distributional changes and the effectiveness of the network of Special Protection Areas (SPAs, EU Birds Directive) in the context of climate change. Location Europe. Methods We used site‐specific counts (6, 883 sites) from 16 countries covering the entire flyway to estimate annual abundance indices and trends at country, region (north‐eastern, central and south‐western) and flyway scales, inside and outside SPAs. We fitted autoregressive models to assess the effect of winter temperature on the annual abundance indices whilst accounting for autocorrelation. Results The Smew wintering distribution shifted north‐eastwards in Europe in accordance with the predictions of global warming, with increasing numbers in the north‐eastern region and declines in the central region. Trends in wintering numbers were more positive in SPAs on the north‐eastern and south‐western part of the flyway. However, a large proportion of the wintering population remains unprotected in north‐eastern areas outside of the existing SPA network. Main conclusions SPAs accommodated climate‐driven abundance changes in the north‐eastern region of the wintering distribution by supporting increasing numbers of Smew in traditional and newly colonized areas. However, we highlight gaps in the current network, suggesting that urgent policy responses are needed. Given rapid changes in species distributions, we urge regular national and international assessments of the adequacy of the EU Natura 2000 network to ensure coherence in site‐safeguard networks for this and other species.